(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
The current work shows a schematic review of the scientific information available on the antiviral effect of the drug ivermectin against SARS-CoV-2 and the pharmacological properties that support this effect. In the context of drug repositioning, the antiviral effect of ivermectin against different viruses has been studied in different in vitro models. From a pharmacodynamic point of view, ivermectin would have an antiviral response that could combine actions on host cells (inhibition of transport across the nuclear membrane) and direct effects on molecular targets of the virus. Different ivermectin administration regimens have been evaluated in various countries around the world as a preventive measure and also as a therapeutic tool against SARS-CoV-2. The results show effects of ivermectin in reducing viral load, in accelerating clinical recovery and preventing deterioration in patients treated in the early stage of the disease, and in reducing the rate of hospitalization and mortality.